2022
DOI: 10.3389/fnbeh.2022.1022713
|View full text |Cite
|
Sign up to set email alerts
|

Temporal scaling and computing time in neural circuits: Should we stop watching the clock and look for its gears?

Abstract: Timing underlies a variety of functions, from walking to perceiving causality. Neural timing models typically fall into one of two categories—“ramping” and “population-clock” theories. According to ramping models, individual neurons track time by gradually increasing or decreasing their activity as an event approaches. To time different intervals, ramping neurons adjust their slopes, ramping steeply for short intervals and vice versa. In contrast, according to “population-clock” models, multiple neurons track … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…In other words, a neural-activity pattern can continuously, not discretely, represent durations of various lengths by changing the transition speed. Therefore, the intermediate peak time can be obtained from the intermediate transition speed (Corte et al, 2022). The above argument was supported by a recent study indicating that the subjective length of duration causally depends on the transition speed of neural-activity pattern in the DS (i.e., slowing the transition of the neural-activity pattern made the rat perceive the duration to be shorter than it was, and vice versa) (Monterio et al, 2023).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In other words, a neural-activity pattern can continuously, not discretely, represent durations of various lengths by changing the transition speed. Therefore, the intermediate peak time can be obtained from the intermediate transition speed (Corte et al, 2022). The above argument was supported by a recent study indicating that the subjective length of duration causally depends on the transition speed of neural-activity pattern in the DS (i.e., slowing the transition of the neural-activity pattern made the rat perceive the duration to be shorter than it was, and vice versa) (Monterio et al, 2023).…”
Section: Discussionmentioning
confidence: 69%
“…Physiological studies suggested that information on the specific duration, such as a required time, was encoded with the transition of the neuralactivity pattern (Bakuhurin et al, 2017;Matell et al, 2003;Mello et al, 2015;Shikano et al, 2021;Zhou et al, 2020). A previous study argued that "temporal scaling" explains how the transition of the neural-activity pattern induces temporal averaging (Corte et al, 2022). They explain that the original neural-activity pattern encoding the original duration can also encode a longer or shorter duration than the original one by increasing or reducing the transition speed of the original neural-activity pattern (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies suggested that information regarding a specific duration, such as the required time, is encoded by the transition of neural activity patterns (Bakhurin et al, 2017; Mello et al, 2015; Shikano et al, 2021; Zhou et al, 2020). A previous study argued that temporal scaling explains how the transition of neural activity patterns induces temporal averaging (De Corte et al, 2022). They explained that the original neural activity pattern encoding the original duration could also encode a longer or shorter duration than the original by reducing or increasing the transition speed of the original neural activity pattern (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a neural activity pattern can continuously represent durations of various lengths by changing the transition speed. Therefore, the intermediate peak time can be obtained from the intermediate transition speed (De Corte et al, 2022). The above argument is supported by a recent study indicating that the subjective duration causally depends on the transition speed of the neural activity pattern in the DS (i.e.…”
Section: Discussionmentioning
confidence: 99%